Antioxidant in Vitro Scavenging Potential of Medicinal Plant- Embelia Basal - Monika V. Jagtap, Dr. Rashmi M. Kenvat, Dr. Gayatri S. Kamble, Dr. Balaji S. Selukar (Mathematical Statistician and Engineering Applications, 2021)
Embelia basal, belonging to family Myrsinaceae, is a well known medicinal plant as mentioned in Ayurvedic system of medicine. Medicinal plants are a source for a wide variety of natural antioxidant. Antioxidant activity is essential for many biological functions. Literature survey revealed that there are no reports on radical scavenging activity of the leaves of E. basal. The present work was carried out in order to evaluate the efficacy of E. basal, in view of free radical scavenging activity using acetone, ethanol, and methanol extracts. Plant material was screened for their antioxidant activity by employing radical scavenging assay; DPPH (2, 2- Diphenyl -1- picrylhydrazyl). The percentage radical activity for the assay was determined using ascorbic acid as a standard. From the standard curves, inhibition concentrations in the test samples were calculated. It can be seen that the DPPH radical scavenging activity for ethanol extract is found to be more significant than methanol and acetone extracts. The findings of the present study suggest that E. basal could be a potential source of natural antioxidant that could have great importance as therapeutic agents in preventing or slowing the progress of aging and age associated oxidative stress related degenerative diseases.